Laporan Posisi Keuangan Umkm Peralatan Rumah Tangga Di Sidoarjo Pasar Permata Tanggulangin Sesuai Dengan Standar Akuntansi Keuangan-Entitas-Mikro, Kecil, dan Menengah (SAK EMKM) - Yoga Hutama Wicaksana; Adeanto Putra Satyatama; Cholifatun Nisa; Nabil Sada Amarie; Sirilia Sesilma Jinate Ruben; Elisabeth Lauboling; Sri Rahayuningsih (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
Financial reporting is one of the important things in a large company or small business (UMKM). While MSMEs themselves have the meaning of micro, small and medium enterprises, MSMEs are regulated based on UUD No. 20 of 2008 concerning micro, small and medium enterprises. Mrs Emi Household Equipment Retail Store Business is part of the Micro Business or MSME which has many great opportunities to develop. However, in carrying out its business processes, financial recording and reporting are still in simple form (manual) even though they are computerized. This research aims to find out and help prepare financial reports for the Mrs. Emi Household Equipment Retail Store Business based on SAK EMKM. The research methods used in this research are descriptive and qualitative methods, because the related information and knowledge used in this research was obtained from direct interviews with micro business owners or MSMEs. In this research, the analysis model used is interactive analysis, which consists of 3 processes, namely data reduction, data presentation, and drawing conclusions. The results of this research can be concluded that the Mrs. Emi Household Equipment Retail Store has not implemented Financial Accounting Standards (SAK) in recording financial transactions, and has not implemented SAK EMKM in preparing financial reports. The preparation of financial reports in this research based on SAK EMKM was carried out by applying the accounting cycle, because it was felt that there was uncertainty in presenting information from previous periods, so the preparation was carried out prospectively using the accrual basic approach.